Advanced Imaging of the Vestibular Endolymphatic Space in Ménière's Disease - Zanetti, Diego; Conte, Giorgio; Scola, Elisa; Casale, Silvia; Lilli, Giorgio; Di Berardino, Federica (Frontiers in Surgery, 2021)
Diagnosis of “definite” Meniere’s disease (MD) relies upon its clinical manifestations. MD has been related with endolymphatic hydrops (EH), a distension of the endolymphatic spaces (ES) of the inner ear (cochlear duct, posterior labyrinth or both). Recent advances in Magnetic Resonance (MR) imaging justify its increasing role in the diagnostic work-up of MD: EH can be consistently recognized in living human subjects by means of a 3D Fluid Attenuated Inversion Recovery sequence, acquired 4 hours after the intravenous (i.v.) administration of gadolinium-based contrast medium by a 3 Tesla scanner, or 24 hours after an intratympanic (IT) injection. Different criteria to assess EH include: the ratio of the area of the vestibular ES to the entire vestibule in the axial plane; the saccule to utricle ratio (“SURI”); and the bulging of the vestibular organs in the third inferior of the vestibule contacting the stapes footplate (“VESCO“). An absolute link between MD and EH has been questioned, since not all patients with hydrops manifest MD symptoms. We performed a systematic review of the literature, reporting the technical refinements of the imaging methods proposed with either IT or i.v. delivery routes, and reviewing the outcomes of MR imaging of the ES in both MD and non-MD patients. Finally, we discuss the imaging findings observed by different researchers, such as the blood-labyrinthine barrier (BLB) breakdown, the extent and grading of EH, its correlation with clinical symptoms, otoneurological tests and stage and progression of the disease.